A study of the Coulomb stress and seismicity rate changes induced by the 2008 Mw 7.9 Wenchuan earthquake, SW China. (March 2017) - Hu, Junhua; Fu, Li-Yun; Sun, Weijia; Zhang, Yan
Graphical abstract: Highlights: Triangular elements avoid singular stresses caused by rectangular elements. The depth of calculation makes a significant difference to the stress change. High background seismicity rates will amplify the effect of stress change. The observed seismicity rate changes verify the forecast rate of 10-year seismicity. Abstract: Correlations between the calculated Coulomb stress changes and observed seismicity rate changes after the Wenchuan earthquake are investigated in this article. Three improvements are made in the calculation of static stress change, including employing a dislocation method with triangular elements rather than traditional rectangular elements, setting up a more realistic source-slip model and a more complete receiver fault model, and resolving stress changes on assumed receiver faults with spatially variable focal mechanisms based on well-determined focal mechanisms at different calculation points. The recorded aftershocks are mapped for comparison with the spatial distribution of stress changes. The results indicate that the Wenchuan earthquake encourages not only three major fault systems (the East Kunlun, south of Xianshuihe and west of Qinling Southern Frontal) but also several other regions including Tazang, north of Min Jiang, north of Pingwu-Qingchuan and west of Chongqing. In particular, the eastern segment of Longriba is shown to be quite dangerous with dramatic stress increase. The influence of depth and frictional coefficient is analyzed. The depth of calculation beyond the depth range of the source model will make a significant difference to the stress-change map and thus cannot be neglected. Many aftershocks occurring in the stress shadow zone near the main rupture can be attributed to dynamic stress triggering and the fractal structure of the main fault. The observed seismicity rate changes are compared with the static stress changes. The results show that high background seismicity rates will amplify the effect of stress change. The observed seismicity rate changes support the forecast rate of 10-year seismicity after the Wenchuan earthquake based on the rate- and state-dependent friction model. Coulomb stresses increase on the focal mechanisms away from the main rupture, which demonstrates the influence of the Wenchuan earthquake over a wide range. Especially, the focal mechanism for Lushan earthquake undergoes a stress increase by more than 2.0 bars, which suggests that the Lushan earthquake has been effectively promoted by the Wenchuan earthquake.